Epidemiology of Animal Bite Injuries in Golestan Province, Northeast of Iran, during 2011-12 - Abdullah Abbasi; Somayeh Azadfar; Gholamreza Roshandel; Roghieh Golsha; Mohammad Naeimi; Behnaz Khodabakhshi; Ali Bagheri; Naghimeh Hajimoradloo (Golestan University Of Medical Sciences, 2017)
Introduction: Animal bite is a public health problem worldwide. The aim of this study was to investigate frequency of animal bites in Golestan province, northeast of Iran, between 2011 and 2012. Methods: This descriptive cross-sectional study was done by collecting data from medical records of animal bite victims referred to the health centers in the Golestan province, in 2011-12. Information collected included species of animals, gender, age, occupation, location of residence, type of treatment, and type of injury. The data were analyzed by SPSS (version 16). Results: Overall, there were 10,810 incidents of animal bites in the province in 2011-12. Of these cases, 8125 (75.48%) were men and most cases were 5-24 years of age. Dog bites accounted for 9885 (91.44%) cases of animal bites. Most incidents occurred in rural areas (82.27%). Most vulnerable individuals were students (n=2370, 21.92%) and homemakers (n=1722, 15.93%). The most common site of animal bites was lower limb (62.53%). Moreover, treatment with anti-rabies serum and vaccine was done for 9610 (89.9%) and 9068 (83.89%) cases, respectively. Conclusions: According to our results, animal bites are more frequent in young men, residents of rural areas, and students. In addition, dog bites account for 91% of all cases of animal bites in the province. These results highlight the need for education programs on animal bites and rabies to increase knowledge and awareness of the individuals at risk.